2014
DOI: 10.1021/ml5001728
|View full text |Cite
|
Sign up to set email alerts
|

Benzimidazoles: Novel Mycobacterial Gyrase Inhibitors from Scaffold Morphing

Abstract: Type II topoisomerases are well conserved across the bacterial species, and inhibition of DNA gyrase by fluoroquinolones has provided an attractive option for treatment of tuberculosis (TB). However, the emergence of fluoroquinolone-resistant strains of Mycobacterium tuberculosis (Mtb) poses a threat for its sustainability. A scaffold hopping approach using the binding mode of novel bacterial topoisomerase inhibitors (NBTIs) led to the identification of a novel class of benzimidazoles as DNA gyrase inhibitors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(35 citation statements)
references
References 7 publications
0
34
0
1
Order By: Relevance
“…Nitrogen containing heterocyclic compounds are pivotal building blocks in natural products, pharmaceuticals and organic/polymeric materials . In particular, benzimidazoles are medicinally important bioactive heterocyclic scaffolds and found to have a broad spectrum of biological and pharmacological properties including anti‐bacterial, anti‐fungal, anti‐inflammatory, anti‐ulcer, anti‐cancer, and anti‐HIV activities . Owing to the parmaceutical importance, various methods have been reported for their synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen containing heterocyclic compounds are pivotal building blocks in natural products, pharmaceuticals and organic/polymeric materials . In particular, benzimidazoles are medicinally important bioactive heterocyclic scaffolds and found to have a broad spectrum of biological and pharmacological properties including anti‐bacterial, anti‐fungal, anti‐inflammatory, anti‐ulcer, anti‐cancer, and anti‐HIV activities . Owing to the parmaceutical importance, various methods have been reported for their synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…The benzimidazole scaffold has also shown anti-mycobacterial activity in vitro [9][10][11][12][13][14] . Ojima et al 15 tuberculosis.…”
mentioning
confidence: 99%
“…[8][9][10]16 The synthesis of compounds with bulky substitutions (2−9) are illustrated in Scheme 1. Nucleophilic displacement of halo substituted naphthyridones (I) with corresponding carbinol (II) using cesium carbonate under thermal heating condition resulted in title compounds 2−19.…”
mentioning
confidence: 99%
“…This design was based on the initial SAR observations made during the lead optimization of NBTIs as novel antimycobacterial agents reported earlier. 16 However, we have not explored similar substitution at C-6 position as the SAR studies suggest that a compound with 6-methoxy substitution was found to be inactive against Mtb. 8 We hypothesized that by lowering the logD and modulation of polarity via bulky polar substitutions on LHS ring may provide structural diversity to mitigate hERG liability.…”
mentioning
confidence: 99%
See 1 more Smart Citation